Raising the curtain : recasting women performers in India - Lata,Singh (Critical thinking in South Asian history, 2017)
Raising the Curtain, through the study of women performers in colonial and Independent India, problematises the question of gender and patriarchy. Women performers, being the most public women, unsettle the category of gender divided along castes, class, sexuality and the private/public paradigm. Women performers do not form a homogenous category; their roles, agency, issues, concerns and lives differ significantly because of their different social and cultural locations. They ranged from the royally patronised nagarbandhu and ganika in ancient India, to the lower-caste performers of popular theatres, to the politically powerful tawaifs in medieval India, to subaltern women actresses in elite theatre of colonial India, to educated middle-class women of the Indian People’s Theatre Movement of the 1940s, whose primary aim was to bring about social and political change. Colonial modernity and middle-class respectability discourse stigmatized and criminalised women performers by creating a fuzzy boundary between them and prostitutes. By foregrounding the status and position of these women in brahmanical/middle-class patriarchal society, the study enters larger debates in feminist and cultural historiographies to understand what marriage, family and domesticity, the middle-class respectability quest meant for women and how actresses have used theatre to carve their own space, identity and labour. This volume also highlights cultural labour, which has remained invisible in mainstream labour history and also devalued in mainstream society because of its linkage with caste, class, gender, sexuality and cultural politics. This problematises the question of sexuality taking the debate beyond sexual choice, agency and autonomy. Through the use of a wide range of sources, this finely crafted book fills a significant gap in the study of subaltern cultural history and feminist historiography. It will be essential reading for scholars and students of subaltern history, sociology, gender studies, as well as of the theatre.